Efficacy and Safety of Zhenyuan Capsule for Coronary Heart Disease with Abnormal Glucose and Lipid Metabolism: Study Protocol for a Randomized, Double-Blind, Parallel-Controlled, Multicenter Clinical Trial. (26th April 2018) - Qiao, Yu; Zhang, Jingchun; Liu, Yue; Liang, Zhiqi; Wang, Yuhua; Zheng, Wei; Shi, Dazhuo
Abstract : Background . Coronary heart disease (CHD) and abnormal glucose and lipid metabolism are closely associated and generally coexist. The Qi and Yin deficiency syndrome is a common disease pattern encountered in traditional Chinese medicine. We designed a protocol to determine the effectiveness and safety of Zhenyuan capsules for CHD with abnormal glucose and lipid metabolism. Methods . This multicenter, randomized, double-blind, parallel-controlled trial was designed in accordance with the CONSORT. We will recruit 200 eligible male patients aged 45–75 years from three participating centers and randomly assign them to treatment and control groups (1 : 1). The primary indicators are glycosylated hemoglobin, fasting blood glucose, 2-hour postprandial blood glucose, and triglyceride levels. The secondary indicators are the Seattle Angina Questionnaire, TCM symptom indicators, ultrasonic cardiography finding, coagulation indicator, and P-selectin level. Measurements will be performed at baseline (T0), the end of the run-in period (T1), and weeks 4 (T2), 8 (T3), and 12 (T4) of the treatment period. Adverse events will be monitored during the trial. Discussion . This study aims to evaluate the efficacy and safety of Zhenyuan capsules in patients with CHD and abnormal glucose and lipid metabolism. The results will provide critical evidence of the usefulness of the Chinese herbal medicine for CHD with abnormal glucose and lipid metabolism. Trial Registration . This trial is registered with the Chinese Clinical Trials Registry, with identifier number ChiCTR-TRC-14004639, May 4, 2014.